Careless Responding Threatens Factorial Analytic Results and Construct Validity of Personality Measure - Kam, Chester Chun Seng (Frontiers in Psychology, 2019)
The current research investigates the impact of careless responding on factorial analytic results and construct validity with real data. Results showed that inclusion of careless respondents in data analysis distorts factor loading pattern and hinders recovery of theoretical existing factors. Careless respondents also blur the distinction of theoretically distinct factors, resulting in higher inter-factor correlations. That careless responding may threaten convergent validity also receives limited support. Researchers are advised to exclude careless respondents before statistical analysis.